ChemInform Abstract: Synthesis of Fused Isoquinolinone and Iminoisoindolinone Derivatives via a Copper‐Catalyzed Regioselective Switching Process. Issue 6 (23rd January 2015) - Kavala, Veerababurao; Wang, Cheng‐Chuan; Wang, Yu‐Hsuan; Kuo, Chun‐Wei; Janreddy, Donala; Huang, Wen‐Chang; Kuo, Ting‐Shen; He, Chiu Hui; Chen, Mei‐Ling; Yao, Ching‐Fa
Abstract In the presence of the strong bases benzyl cyanide derivatives (II) act as nucleophiles yielding fused isoquinoline derivatives.